Studi Performansi Las Gesek Rotary Pada Penyambungan Mild Steel Dengan Stainless Steel 201 - Rasyid, Kurniawan; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Friction welding is a type of solid state welding with high quality results from two components that are similar or different so that it attracts a lot of attention. With phenomena that occur during welding, the finite element method becomes a very appropriate method to be developed in this welding process. In appropriate and easily simplified settings, this method is simulated in Finite Element Method based applications. Based on previous observations and research, the right time to provide forging loads on welding is very difficult to determine. For that we need to do a simulation before doing welding so that we can get a picture to do welding with good results, and with this simulation it is also expected to be able to know the temperature propagation in the specimen against the welding time.Keywords : Friction Welding, Simulasi, Finite Element, Dissimilar Material, Timing of Diffusion.